Age‐related changes in visual contour integration: Implications for physiology from psychophysics. Issue 6 (27th May 2014) - Hipp, D.; Dickerson, K.; Moser, A.; Gerhardstein, Peter
ABSTRACT Visual contour detection is enhanced by grouping principles, such as proximity and collinearity, which appear to rely on horizontal connectivity in visual cortex. Previous experiments suggest that children require greater proximity to detect contours and that, unlike adults, collinearity does not compensate for their proximity limitation. Over two experiments we test whether closure, a global property known to facilitate contour detection, compensates for this limitation. Adults and children (3–9 years old) performed a 2AFC task; one panel contained an illusory contour (closed or open) in visual noise, and one only noise. The experiments were identical except proximity was doubled in Exp. 2, enabling shorter‐range spatial integration. Results suggest children are limited by proximity, and that closure did not reliably improve their performance as it did for adults. We conclude that perceptual maturity lags behind anatomy within this system, and suggest that slow statistical learning of long‐range orientation correlations controls this disparity. © 2014 Wiley Periodicals, Inc. Dev Psychobiol 56: 1390–1405, 2014.